BIODIESEL AS A LUBRICITY ADDITIVE FOR DIESEL FUEL - Pallawagau La Puppung (Testing Center for Oil and Gas LEMIGAS, 2007)
Sulfur in diesel fuel will influence particulate matter emission either in exhaust gasflow or in atmosphere. The other effect of sulfur it can cause corrosion and engine wear.Further, sulfur also can influence on catalytic system in exhaust pipe. Due to this reasonsulfur level in diesel fuel should be set as lower as possible. The process can be used toreduce sulfur level is desulfurization process (hydrotreatment). At the hydrotreatment todesulfurize diesel fuel, lubricity can decrease, it is cause by reduction of fuel componentswhich have good natural lubricity.Lubricity, is very relevant to the satisfactory operation of diesel fuel engines whichrelay on the fuel to lubricate many of the moving and rubbing metal parts of the fuelinjection equipment. Some injection equipment may be at risk if operated on fuels of lowlubricity.Biodiesel as results of transesterification has a good lubricity, the test results of addingbiodiesel into a lower lubricity of diesel fuel indicate that biodiesel can be used to increasediesel fuel lubricity.